The origin and evolution of the parental magmas of frontal volcanoes in Kamchatka: Evidence from magmatic inclusions in olivine from Zhupanovsky volcano. - Plechova, Anastasiya A; Portnyagin, Maxim V; Bazanova, L (PANGAEA, 2011)
The paper presents data on naturally quenched melt inclusions in olivine (Fo 69-84) from Late Pleistocene pyroclastic rocks of Zhupanovsky volcano in the frontal zone of the Eastern Volcanic Belt of Kamchatka. The composition of the melt inclusions provides insight into the latest crystallization stages (~70% crystallization) of the parental melt (~46.4 wt % SiO2, ~2.5 wt % H2O, ~0.3 wt % S), which proceeded at decompression and started at a depth of approximately 10 km from the surface. The crystallization temperature was estimated at 1100 ± 20°C at an oxygen fugacity of deltaFMQ = 0.9-1.7. The melts evolved due to the simultaneous crystallization of olivine, plagioclase, pyroxene, chromite, and magnetite (Ol: Pl: Cpx : (Crt-Mt) ~ 13 : 54 : 24 : 4) along the tholeiite evolutionary trend and became progressively enriched in FeO, SiO2, Na2O, and K2O and depleted in MgO, CaO, and Al2O3. Melt crystallization was associated with the segregation of fluid rich in S-bearing compounds and, to a lesser extent, in H2O and Cl. The primary melt of Zhupanovsky volcano (whose composition was estimated from data on the most primitive melt inclusions) had a composition of low-Si (~45 wt % SiO2) picrobasalt (~14 wt % MgO), as is typical of parental melts in Kamchatka and other island arcs, and was different from MORB. This primary melt could be derived by ~8% melting of mantle peridotite of composition close to the MORB source, under pressures of 1.5 ± 0.2 GPa and temperatures 20-30°C lower than the solidus temperature of 'dry' peridotite (1230-1240°C). Melting was induced by the interaction of the hot peridotite with a hydrous component that was brought to the mantle from the subducted slab and was also responsible for the enrichment of the Zhupanovsky magmas in LREE, LILE, B, Cl, Th, U, and Pb. The hydrous component in the magma source of Zhupanovsky volcano was produced by the partial slab melting under water-saturated conditions at temperatures of 760-810°C and pressures of ~3.5 GPa. As the depth of the subducted slab beneath Kamchatkan volcanoes varies from 100 to 125 km, the composition of the hydrous component drastically changes from relatively low-temperature H2O-rich fluid to higher temperature H2O-bearing melt. The geothermal gradient at the surface of the slab within the depth range of 100-125 km beneath Kamchatka was estimated at 4°C/km.
Major and trace element concentration of melt inclusions from Zhupanovsky volcano, Kamchatka
Keywords: Archive of Ocean Data; ARCOD; HAND; Sampling by hand; Zhupanovsky